Swallowing the RFId pill: the redesign of a pharmaceutical wholesaler supply chain. (2nd November 2010) - Miragliotta, Giovanni; Perego, Alessandro; Tumino, Angela
Radio frequency identification (RFId) technology promises to offer both a more efficient and accurate tracking and tracing of goods, as well as a reduction in thefts and counterfeiting in the pharmaceutical supply chain. Attracted by this opportunity, numerous companies that are carrying out pilot projects in this supply chain are focusing on item-level applications. Unfortunately, these applications remain somewhat futuristic for both technological and economic reasons. However, little attention has been paid to case-level tagging, which can help improve logistics. Moreover, the role of process redesign and of supply chain integration has not been quantitatively explored. This paper, taking the angle of the wholesaler of pharmaceutical goods, presents an activity-based model to evaluate the costs and benefits that stem from the adoption of RFId at the case level, and analyses how the investment profitability is affected by supply chain integration, process redesign, initial level of efficiency and technology reliability.